Thermo-metallo-mechanical modelling of heat treatment induced residual stress in Ti–6Al–4V alloy. Issue 7 (3rd May 2019) - Rae, W.
ABSTRACT: Residual stress fields dynamically fluctuate throughout the manufacturing process of metallic components and are caused by local misfit of a thermal, mechanical or metallurgical nature. Recent advances have been made in the area of microstructure and residual stress prediction; yet few have considered dual-phase titanium alloys. The aim of the work presented was to carry out a review of the existing state-of-the-art in residual stress modelling with an intended application to industrial heat treatment of Ti–6Al–4V alloy. Four areas were evaluated: thermal, mechanical and metallurgical sub-models, and model validation via residual stress measurement. Recommendations for future research include further investigation of transformation induced plasticity and stress relaxation behaviour in Ti–6Al–4V. This review was submitted as part of the 2019 Materials Literature Review Prize of the Institute of Materials, Minerals and Mining run by the Editorial Board of MST. Sponsorship of the prize by TWI Ltd is gratefully acknowledged.